India’s Strategic Autonomy and the Dilemma of the Ukraine War - Hazarika, Kundan (Journal of Innovation in Education and Social Research, 2023)
Russia's 2022 invasion of Ukraine created a profound dilemma for India, pitting its long-standing strategic partnership with Moscow against its deepening ties with the West. While Western powers enacted a comprehensive sanctions regime and condemned Russia's aggression, India adopted a position of calculated neutrality, consistently abstaining from critical votes at the United Nations and refusing to join sanctions. This article argues that India's response is not a nostalgic remnant of Cold War-era non-alignment, nor is it a tacit endorsement of Russian actions. Instead, it is the deliberate application of a post-Cold War foreign policy doctrine of "strategic autonomy." This doctrine is driven by a realpolitik assessment of India's core national interests in a fluid, multipolar world. The paper posits that India's stance is primarily shaped by two overriding imperatives: the structural dependency on Russia for military hardware, which is critical for national defense against China and Pakistan; and the strategic necessity of preventing a deeper Sino-Russian axis that would fundamentally undermine India's security. New Delhi’s policy, therefore, represents a calculated prioritization of its immediate and long-term regional security challenges over taking a normative position in a distant conflict, even at the cost of significant diplomatic friction with its Western partners.